Voices of the Trail: Trauma, Memory, Identity, and Resilience in Robert J. Conley’s Mountain Windsong - Sharma, Shyam Prasad (Dhaulagiri Journal of Contemporary Issues, 2025)
Robert J. Conley’s Mountain Windsong: A Novel of the Trail of Tears gives voice to the marginalized Cherokee people, spotlighting their trauma, resistance, and cultural identity during the forced relocation known as the Trail of Tears. Blending historical fiction with a modern frame narrative, the novel uses oral storytelling through a grandfather passing tales to his grandson to preserve memory, resist dominant historiography, and reinforce indigenous identity. It reclaims the forgotten history of Native Americans by incorporating legends, songs, anecdotes, and historical documents that reflect the Cherokee oral tradition. Set between 1835 and 1838, the novel recounts the brutal displacement of nineteen thousand Cherokees from North Carolina to Indian Territory in Oklahoma, where over four thousand died from hunger, illness, and violence. Among these tragic events, the painful separation of lovers Oconeechee and Waguli highlights the personal cost of this collective trauma. Through fragmentation and narrative layering, Conley deconstructs grand historical narratives and reveals the deep psychological and cultural wounds inflicted by white American policies. This study, using a qualitative, text-based analytical method, examines themes of trauma, memory, resistance, and cultural survival in the face of genocidal violence. Theoretical frameworks include insights from Trauma Studies (Caruth, LaCapra, Kaplan), Genocidalism (Huttenbach, Mosham), Postcolonialism (Said, Bhabha), Subaltern Studies, and narrative theory (Elias, White). Mountain Windsong emerges as a powerful literary testimony to Cherokee resilience and a reclamation of silenced history, exploring how collective memory and storytelling sustain identity through generations.